Development of constructivism-based physics tools to build generic science skills for high school students - Ardiansyah Ardianyah (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
This research and development aim to develop constructivism-based physics teaching aids to build students' generic science skills on static fluid material. The research subjects chosen were class XI Senior High School 2 Kilo, semester I, studying static fluid material for the 2022/2023 academic year. The validation results for the development of constructivism-based physics teaching aids to build Generic Science Skills for high school students on static fluid material show an average score of 0.75 with a percentage of 22.43% for very good criteria, an average score of 2.75 with a percentage of 78.57% for good criteria. At the same time, the categories are sufficient, lacking, and very unfavorable, each with an average score of 0 with a percentage of 0.00%. It indicates that the validator assesses the aspect of the teaching aids as good. The development of constructivism-based physics teaching aids on static fluid material can build students' Generic Science Skills, shown in the N-Gain percentage of 70.65% with the high category. Students also responded positively to the development of constructivism-based teaching aids in building Generic Science Skills. It was indicated by the average student responding strongly agree 37.60% and giving a response of agree 44.00% while responding disagree 9.80%, strongly disagree 8.60%.